Orthodontic traction of impacted maxillary canines using segmented arch mechanics - Schroeder,Marco Antonio (2019)
ABSTRACT The principles of orthodontic mechanics strongly influence the success of impacted canine traction. The present study discusses the main imaging exams used for diagnosis and localization of impacted canines, the possible associated etiological factors and the most indicated mechanical solutions.